Rapidly Relocating Molecules Between Organelles to Manipulate Small GTPase Activity - Phua, Siew Cheng (2012)
Chemically-inducible rapid manipulation of small GTPase activity has proven a powerful approach to dissect complex spatio-temporal signaling of these molecular switches. However, overexpression of these synthetic molecular probes freely in the cytosol often results in elevated background activity before chemical induction, which perturbs the cellular basal state and thereby limits their wide application. As a fundamental solution, we have rationally designed and newly developed a strategy to remove unwanted background activity without compromising the extent of induced activation. By exploiting interaction between a membrane lipid and its binding protein, target proteins were translocated from one organelle to another on a time scale of seconds. This improved strategy now allows for rapid manipulation of small GTPases under a physiological state, thus enabling fine dissection of sophisticated signaling processes shaped by these molecules.